Biologic Agents for Treatment of Rheumatoid Arthritis - Butun, Bulent (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2010)
Rheumatoid arthritis (RA) is a chronic disease characterized by an immune mediated inflammatory synovitis that leads to joint destruction, functional impairment, and reduced quality of life. Thus, treatment goals should be longterm substantial relief of pain, arrested joint inflammation and damage, and improved function. Conventional (nonbiologic) DMARDs use is the first step of this debilitating disease treatment but in many patients, this is inadequate and other forms of therapy are required. Advances in the current knowledge of pathogenetic mechanisms of rheumatoid arthritis have contributed to the development of biological therapy, and translated research findings into clinical practice. TNF-alpha (infliximab, etanercept, adalimumab), IL-1 (anakinra) and IL-6 (tocilizumab) inhibitors, a B-cell depleting agent (rituximab) and a drug blocking T-cell costimulation (abatacept) have been approved for rheumatoid arthritis. In this text, the biologic therapies which are currently used in the patients with RA will be reviewed in the company of latest evidences.
Keywords: Rheumatoid arthritis